Rol de los padres de familia en el proceso de enseñanza - aprendizaje de sus hijos - Ganoza Vásquez, Yrene Grace (2007)
A parent who understands its educational work to his offspring, is a parent who contributes to the welfare of the individual and society. This information is for those seeking radical change society through a cultured and progressive nation. Education is a public good in which the greater responsibility for the educational system lies with the state, even if the obligation to educate children is the parents. Hence our interest in education is twofold: as parents and as citizens. But even as parents we care about the education system as a whole, since this affects the quality of education our children receive. Hence the information that we obtain the education system is important to make decisions on questions such as: What kind of education I want for my children? What school should I enroll? Once they are studying Do keep in school where they are or change? If I want to change school at what I can do? And a very important question: What else I can do to improve the education they receive my children? In an eminently changing world, in which the transformations occur constantly in the most diverse areas of life, it is essential to the mission of a comprehensive education that realize the need to develop skills and cognitive skills, but above all, form future generations with values ​​and in touch with their emotions and feelings more emphatic. In this context, the committed participation of parents is essential and irreplaceable. Traditionally it deposited in school responsibility for educating children and young people, without establishing an important link with the family, first experience of training. Several studies have shown that parental involvement in their children's education strongly affects them to improve their academic performance and behavior, have a more positive attitude also contributes to their healthy emotional and emotional development. Cooperation and joint work between family and school seem to point out the path of comprehensive development. The different actors of educational communities, including those who run establishments also realize the importance of parents and guardians in the education of children and youth. I consider fundamental, because we want to reach the family, because there are many factors that influence the learning process of children; for example, often negatively impacts that are not flared in the house. There are moms who work all day; The challenge, then, is how to get those moms can go also working, not in school, but they become educators of their children, she says about Mana Eliana Rebolledo, director of State Educational Institution. There are various instances where parents and guardians can participate in school communities: Associations parents, school advisory councils and even more specific instances such as meetings or extra-curricular activities course. At the same time, each of these instances has its own dynamics and their particular policy areas. The important thing is to understand that no one but various ways in which parents can affect this area: from the most basic and essential as assist the student in the learning process, to influence from other areas such as the management team, on school boards or any other platform that is intended to contribute to a proper progress of the educational community. Especially in the poorest sectors, often the main obstacle to the participation of parents in this area is its situation. It happens that many homes are parenting, usually in charge of you mother, who has to be multiplied to financially support the family and, perhaps, devote time to their children in their education and development process monkey. This reality that the father figure is absent. those cases are added when the father is, but it is a negative influence. "In general, all school initiatives aimed precisely at helping people-exposed to more risk and more helpless Participation is a way;. Through her parents feel valued and can contribute to school